2015
DOI: 10.1007/7854_2015_369
|View full text |Cite
|
Sign up to set email alerts
|

Animal Studies on the Role of Sleep in Memory: From Behavioral Performance to Molecular Mechanisms

Abstract: Although the exact functions of sleep remain a topic of debate, several hypotheses propose that sleep benefits neuronal plasticity, which ultimately supports brain function and cognition . For over a century, researchers have applied a wide variety of behavioral, electrophysiological, biochemical, and molecular approaches to study how memory processes are promoted by sleep and perturbed by sleep loss. Interestingly, experimental studies indicate that cognitive impairments as a consequence of sleep deprivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 101 publications
1
50
1
Order By: Relevance
“…The cyclic AMP (c-AMP)/protein kinase A (PKA)/c-AMP response element binding protein (CREB) pathway plays an important role in synaptogenesis and synaptic plasticity [135]. Although the c-AMP /PKA/CREB pathway is not the focus of this review, it is important to note its cross-talk with phospholipase C (PLC)/PKC signaling pathway.…”
Section: Downstream Targets Of Pkcmentioning
confidence: 99%
“…The cyclic AMP (c-AMP)/protein kinase A (PKA)/c-AMP response element binding protein (CREB) pathway plays an important role in synaptogenesis and synaptic plasticity [135]. Although the c-AMP /PKA/CREB pathway is not the focus of this review, it is important to note its cross-talk with phospholipase C (PLC)/PKC signaling pathway.…”
Section: Downstream Targets Of Pkcmentioning
confidence: 99%
“…Recent work (Wellman et al, 2016) and the current study also demonstrate that individual outbred rats can show either decreases or increases in REM in response to IS, also without differences in freezing or SIH. Thus, while several studies have demonstrated that sleep may play a role in the consolidation of contextual fear memory associated with brief or mild fearful experiences (e.g., Graves, Heller, Pack, and Abel, 2003; Greenwood, Thompson, Opp, and Fleshner, 2014; Hagewoud, Bultsma, Barf, Koolhaas, and Meerlo, 2011; Hellman and Abel, 2007; Kumar and Jha, 2012; Menz, Rihm, and BĆ¼chel, 2016; Menz, Rihm, Salari, Born, Kalisch, Pape, Marshall, and Buchel, 2013; Rossi, Tiba, Moreira, Ferreira, Oliveira, and Suchecki, 2014; Silvestri, 2005; for recent review see Havekes, Meerlo, and Abel, 2015), there is no evidence that REM sleep is necessary for the formation of contextual fear memory associated with relatively intense stressful experiences. Interestingly, we found no correlation between freezing and either REM or NREM sleep.…”
Section: 0 Discussionmentioning
confidence: 99%
“…[58][59][60][61][62] Sleep also appears necessary for memory, with sleep deprivation leading to decrements in cognitive performance and memory impairments. 4,[63][64][65] Additionally, sleep following learning can enhance memory strength, particularly for hippocampal-dependent learning in humans and animal models. [66][67][68][69] Invertebrates, with their comparatively simple nervous system, have proven invaluable for elucidating the molecular mechanisms underlying complex behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Acute sleep deprivation and chronic sleep restriction cause significant decrements in short-term and long-term memories in humans and in animal models. [3][4][5][6][7][8][9] In mammals, the consolidation of hippocampal dependent spatial memory is particularly susceptible to the effects of sleep deprivation. [10][11][12] In Drosophila and mouse models, genetic mutants exhibiting reduced sleep also show impairments in memory.…”
Section: Introductionmentioning
confidence: 99%